A DFT/TDDFT Investigation of Excited State Dynamical Mechanism of (E)‐1‐((2, 2‐Diphenylhydrazono)methyl)naphthalen‐2‐ol. Issue 12 (16th October 2017) - Yang, Dapeng; Wu, Jingyuan; Jia, Min; Song, Xiaoyan
Abstract : The excited‐state intramolecular proton transfer (ESIPT) mechanism of a new compound ( E )‐1‐((2, 2‐diphenylhydrazono)methyl)naphthalen‐2‐ol (EDMN ) sensor, reported and synthesized by Mukherjee et al . [ Sensors Actuat. B‐Chem . 2014, 202, 1190], is investigated in detail theoretically. The calculations on primary bond lengths, bond angles, and the corresponding infrared (IR) vibrational spectra and hydrogen‐bond energy involved in intramolecular hydrogen bond between the S0 and S1 states confirm that the intramolecular hydrogen bond is strengthened in the S1 state, which reveals the tendency of ESIPT reaction. The fact that the experimental absorption and emission spectra are well reproduced demonstrates the rationality and effectiveness of the time‐dependent density functional theory (TDDFT) level of theory we adopt here. Furthermore, intramolecular charge transfer based on the frontier molecular orbitals (MOs) gives indication of the ESIPT reaction. The constructed potential energy curves of both the S0 and S1 states while keeping the O─H distance ofEDMN fixed at a series of values are used to illustrate the ESIPT process. The lower barrier of ~3.934 kcal/mol in the S1 state potential energy curve (lower than the 8.254 kcal/mol in the S0 state) provides the transfer mechanism. Abstract : The strengthening intramolecular hydrogen bond in the S1 state provides the possibility for the proton transfer process. The redistribution of charge upon the excitation facilitates the ESIPT reaction. The lower potential energy barrier in the S1 state promotes the ESIPT process, which successfully explains the fluorescence quenching phenomenon.